Influence of Magnesium Oxide Nanoparticles on the Compressive Strength of Urea Formaldehyde Resin - KC, Susma; Rai, Nelson; Shah, Sambridhi; Joshi, Rajendra; Raut, Naresh; Pradhanang, Situ Shrestha; Pandit, Rajesh (Journal of Nepal Chemical Society, 2022)
Urea Formaldehyde (UF) resins have good chemical resistivity and high thermal stability, making them an excellent choice in the construction industry. They, however, pulverize quickly and have low strength and toughness. In this work, magnesium oxide (MgO) nanoparticles were added to UF as nanofillers to influence its compressive strength. MgO nanoparticles were synthesized by reducing magnesium nitrate at different concentrations, using orange peel extract. X-ray Diffraction (XRD) and Fourier Transform Infrared (FTIR) techniques were used to confirm the formation of MgO nanoparticles. XRD results showed the formation of 43 nm, 35.28 nm, and 32.5 nm sized nanoparticles for 0.1 M, 0.2 M, and 0.4 M concentrations respectively. The varying-sized MgO nanoparticles were used for the preparation of UF/MgOnanocomposite at different weight-percentage (wt-%) ratios. A comparative study on the compressive strength of Urea Formaldehyde resins and UF/MgO was performed. From the results, it was found that the addition of MgO nanoparticles to UF resin enhances the compressive strength at certain wt-% ratios.